2019
DOI: 10.1002/adem.201901102
|View full text |Cite
|
Sign up to set email alerts
|

In Operando Monitoring by Analysis of Backscattered Electrons during Electron Beam Melting

Abstract: Additive manufacturing by electron beam melting (EBM) is a complex process, which still lacks reliable tools for process monitoring. Demanding processing conditions such as high temperature, high vacuum, and X‐ray radiation impede the continuous operation of standard process monitoring devices such as light‐optical camera systems. To overcome this deficit, the detection of backscattered electrons (BSEs) is a highly promising approach. A detection system for BSEs is used for recording the in operando signal dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Arnold et al (2019) used the same approach, but only using backscattered electrons, and installed a circular backscattered electron detector shortly above the build chamber of an Arcam S12 machine. Arnold et al (2019) demonstrated that this configuration enabled a much higher spatial resolution (60 µm/pixel). In this study, and in all previously mentioned studies, the electronic image was generated at the end of the melting phase by performing a raster scan of the entire build area with the electron beam.…”
Section: Blade Mounted Sensorsmentioning
confidence: 97%
See 2 more Smart Citations
“…Arnold et al (2019) used the same approach, but only using backscattered electrons, and installed a circular backscattered electron detector shortly above the build chamber of an Arcam S12 machine. Arnold et al (2019) demonstrated that this configuration enabled a much higher spatial resolution (60 µm/pixel). In this study, and in all previously mentioned studies, the electronic image was generated at the end of the melting phase by performing a raster scan of the entire build area with the electron beam.…”
Section: Blade Mounted Sensorsmentioning
confidence: 97%
“…In this study, and in all previously mentioned studies, the electronic image was generated at the end of the melting phase by performing a raster scan of the entire build area with the electron beam. Arnold et al (2019) demonstrated, instead, that the same image could be generated during the melting phase, leading to an 'in-operando' monitoring capability. Along the direction orthogonal to the scan tracks, the resulting image resolution was equivalent to the hatch spacing (between 50 µm/pixel and 100 µm/pixel in the published work).…”
Section: Blade Mounted Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the combined effect of high vacuum and preheating can cause sublimation of metallic elements and further condensation of metal vapors on the surrounding build area surfaces, such as the heat shields, known as metalization [20,21]. The metalization behavior of Al and its effect in TiAl was documented in an earlier study by Cormier et al [22], who showed an Al content decrease of up to 7 at% in the fabricated part compared to the original powder.…”
Section: Introductionmentioning
confidence: 96%
“…Arnold et al [27] extended and tuned the method, showing the capability to achieve a quite high spatial resolution in the measurement of the solidified layer. Arnold et al [28] demonstrated that the same approach could be generated during the melting phase, leading to an "in operando" monitoring capability. Although being potentially suitable to characterize the homogeneity of the powder bed, the electronic imaging method has so far been studied mainly for the characterization of the solidified material in the layer.…”
Section: Introductionmentioning
confidence: 99%